High-durability asphalt additive for both mid-low and high temperatures, asphalt mixture comprising the same, and paving method thereof

The asphalt additive with a microencapsulated process oil and chemical network structure addresses thermal oxidation and bonding issues, ensuring durability and environmental sustainability by maintaining flexibility and strengthening interfacial bonding.

KR103040527B1Active Publication Date: 2026-10-30YOUNCHANG ENC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020260088473
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-05-15
Publication Date
2026-10-30
Estimated Expiration
2046-05-15

AI Technical Summary

Technical Problem

Existing asphalt pavements face issues with thermal oxidation hardening, reduced interfacial bonding strength between heterogeneous aggregates, and environmental impact due to high production temperatures, leading to premature deterioration and increased maintenance costs.

Method used

A method for manufacturing a high-durability asphalt additive using a composite composition with process oil microencapsulated in a porous medium, combined with a three-dimensional network structure formed by chemical bonding, which includes a polyfunctional aziridine-based crosslinking agent and a benzofuranone-based lactone derivative, to maintain flexibility and strengthen bonding at both medium-low and high temperatures.

Benefits of technology

The asphalt additive maintains low-temperature flexibility, prevents cracking, and enhances interfacial bonding strength, significantly extending pavement lifespan and reducing environmental impact by allowing production at lower temperatures with improved durability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112026059408390-PAT00001
    Figure 112026059408390-PAT00001
  • Figure 112026059408390-PAT00002
    Figure 112026059408390-PAT00002
  • Figure 112026059408390-PAT00003
    Figure 112026059408390-PAT00003
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a high-durability asphalt additive suitable for both medium-low and high temperatures, a method for manufacturing an asphalt mixture containing said additive, and an asphalt construction method using said asphalt mixture. Through a mechanism for controlling the oil release rate within the additive and the synergy of crosslinking and anti-oxidation components, it has the effect of suppressing asphalt aging during long-term use and fundamentally preventing plastic deformation and pothole formation caused by heavy loads. Furthermore, through a surface modification process, the chemical interfacial bonding strength between the aggregate and the binder is maximized even in heterogeneous aggregate environments, thereby completely preventing the peeling and detachment of the mixture caused by moisture. Moreover, through the paving construction process using the above asphalt mixture, stable support within the pavement layer can be secured while simultaneously enhancing the structural stability of the pavement.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a high-durability asphalt additive suitable for medium-low and high temperatures, a method for manufacturing an asphalt mixture containing said additive, and an asphalt construction method using said asphalt mixture. Background Technology

[0003] Asphalt pavements are continuously exposed to various environmental factors, such as repetitive heavy loads from vehicles, rainfall, and heavy snowfall, during service. This frequently leads to critical damage, such as plastic deformation, cracking, and potholes caused by moisture penetration. Conventionally, antioxidants or wax-based additives were introduced to ensure the durability of these pavements; however, these methods had limitations as they could not fundamentally prevent the thermal oxidation hardening of the asphalt binder during long-term service, resulting in increased brittleness of the asphalt. In particular, a chronic problem remains where patches or overlay layers laid for the maintenance of aging pavements easily separate and detach due to their short lifespan.

[0004] Meanwhile, in the construction industry, there has recently been a widespread increase in the use of artificial aggregates, such as ferronickel slag, mixed with natural aggregates, such as basalt, for the purpose of resource recycling and reducing construction costs. However, these heterogeneous aggregates have a fatal disadvantage in that their surface chemical properties (transition metals, silicates, etc.) and physical roughness are completely different, resulting in significantly reduced interfacial affinity with asphalt binders, and when moisture penetrates, the bonding strength between the aggregate and the binder is lost, accelerating the delamination phenomenon in which the aggregate is torn off from the surface.

[0005] At the same time, the construction industry is facing the global challenge of carbon neutrality and eco-friendliness. Conventional asphalt mixtures are primarily produced at high temperatures of 150 to 180°C, which entails massive fuel consumption and the emission of harmful gases such as carbon dioxide, and are identified as a major cause of environmental burden. To address this, additives for medium-to-low temperatures with lower production temperatures are being introduced; however, these have limitations, such as difficulty in reliably guaranteeing the quality of asphalt mixtures, reduced compaction during construction, and decreased water resistance.

[0006] Furthermore, depending on the usage environment, various types of functional pavements—such as modified asphalt, permeable, waterproof, and SMA—are required alongside general pavements on-site; however, existing additives present a chronic problem that severely hinders resource recycling and production efficiency because separate products and mix designs must be applied individually for each special application.

[0007] Therefore, there is an urgent need to develop advanced additives and formulation technologies that can be universally applied to modified, SMA, PSMA, waterproof, low-noise drainage, and low-noise non-drainage products by ensuring stable quality at both medium-low and high temperatures without being constrained by production temperature, thereby drastically reducing environmental burden and production costs, while maximizing strong interfacial bonding between dissimilar aggregates and anti-thermal oxidation aging efficacy. The problem to be solved

[0009] One aspect provides a method for manufacturing a highly durable asphalt additive for medium-low and high temperatures.

[0010] Another aspect provides an asphalt additive characterized by being manufactured by the above-described manufacturing method.

[0011] Another aspect provides a method for manufacturing an asphalt mixture having enhanced interfacial bonding strength, comprising the above-mentioned asphalt additive.

[0012] Another aspect provides an asphalt mixture characterized by being manufactured by the above-described manufacturing method.

[0013] Another aspect provides an asphalt construction method using the above-mentioned asphalt mixture. means of solving the problem

[0015] One aspect provides a method for manufacturing a highly durable asphalt additive for both medium-low and high temperatures.

[0016] Specifically, (a) a step of preparing a first mixture by mixing and aging 10 to 30 parts by weight of process oil and 3 to 7 parts by weight of plasticizer with respect to 100 parts by weight of elastic modifier; (b) a step of preparing a second mixture by mixing 5 to 30 parts by weight of process oil with respect to 100 parts by weight of a porous medium containing recycled urethane chips and aging for 20 to 30 hours; (c) a step of preparing a third mixture by mixing 10 to 30 parts by weight of process oil with respect to 100 parts by weight of tackifying resin; (d) a step of mixing and stirring the first mixture, the second mixture, and the third mixture; (e) a step of obtaining an additive base mixture by adding an aged silica sand mixture to the stirred product, wherein 50 to 150 parts by weight of ethylene vinyl acetate (EVA) is mixed with respect to 100 parts by weight of elastic modifier and 0.1 to 0.5 parts by weight of process oil is mixed with respect to 100 parts by weight of silica sand. and (f) a chemical crosslinking and stabilization step comprising adding 0.5 to 4.0 parts by weight of a polyfunctional aziridine-based crosslinking agent and 0.1 to 1.5 parts by weight of a benzofuranone-based lactone derivative to the additive base mixture based on 100 parts by weight of the elastic modifier, and fusing and stirring at a temperature of 90 to 130°C. The present invention provides a method for manufacturing a high-durability asphalt additive suitable for medium-low and high temperatures, comprising: (f) a chemical crosslinking and stabilization step in which 0.5 to 4.0 parts by weight of a polyfunctional aziridine-based crosslinking agent and 0.1 to 1.5 parts by weight of a benzofuranone-based lactone derivative are added to the additive base mixture and fused and stirred at a temperature of 90 to 130°C.

[0017] In step (a) above, this is a process of preparing a first mixture to secure the basic flexibility of the asphalt additive. Specifically, by mixing 10 to 30 parts by weight of process oil and 3 to 7 parts by weight of plasticizer with 100 parts by weight of an elastic modifier, which is a polymeric elastomer, and aging the mixture, the free volume between polymer chains is increased, thereby changing the phase of the modifier from a hard solid state to a flexible state that is easy to mix, and forming a basic base for homogeneous mixing in subsequent processes.

[0018] In this specification, “asphalt” refers to a binder component that binds aggregates together within an asphalt mixture, and may be used interchangeably with asphalt binder or binder.

[0019] In this specification, "elastic modifier" is a general term for polymeric materials added to improve the temperature sensitivity of asphalt and to impart resistance to plastic deformation, and in the present invention, it has significance as a main raw material that forms the basic framework of an asphalt mixture and improves dynamic stability.

[0020] Specifically, the elastic modifier may be styrene-butadiene-styrene (SBS), styrene-isoprene-styrene (SIS), styrene-butadiene rubber (SBR), or polyethylene-based resin, and more specifically, may be styrene-butadiene-styrene (SBS), but is not particularly limited thereto.

[0021] In this specification, "process oil" refers to a softening agent component added to improve the processability of polymeric materials and to control viscosity. In the present invention, it is significant as a key material that not only imparts initial flexibility to elastic modifiers but also encapsulates them within a porous medium to induce sustained release during use. Through this, the low-temperature flexibility of asphalt can be continuously maintained even after long-term use, and cracking caused by thermal oxidative aging can be permanently suppressed.

[0022] Specifically, the process oil may be an aromatic oil, a naphthenic oil, or a paraffinic oil, but is not specifically limited thereto.

[0023] In this specification, "plasticizer" is a general term for an additive that weakens the intermolecular forces of a polymer material to improve moldability and fluidity. In the present invention, it is introduced into the mixing process of an elastic modifier and process oil (first mixture preparation step) to help melt the elastic modifier and ensure homogeneous dispersion, thereby maximizing processing efficiency.

[0024] Specifically, the plasticizer may be a phthalic acid ester-based, adipic acid ester-based, or phosphate ester-based plasticizer, but is not particularly limited thereto.

[0025] In step (b) above, this is a key process for imparting a sustained-release function by supporting process oil inside a porous medium, and a second mixture is prepared by mixing and aging 5 to 30 parts by weight of process oil with 100 parts by weight of a porous medium containing recycled urethane chips, and the optimal aging time for oil absorption within the medium may be 20 to 30 hours.

[0026] In one experimental example, it was confirmed that when the aging time is less than 20 hours, the physical residence time for the oil to penetrate deep into the micropores is insufficient, resulting in a sharp decrease in encapsulation efficiency and reduced long-term aging resistance, whereas when it exceeds 30 hours, the additional performance improvement reaches a saturation state.

[0027] In this specification, "porous medium" refers to a material capable of absorbing and containing liquid substances by including numerous fine pores within it. In the present invention, it serves as a key carrier that encapsulates process oil within the pores and induces its sustained release over a long period upon exposure to the external environment.

[0028] Specifically, the porous medium may be porous silica, zeolite, activated carbon, perlite, or recycled urethane chips, and specifically, may be a porous material made of organic polymer, such as a recycled urethane chip, a porous EPDM rubber chip, or a porous EVA chip, and more specifically, may be a recycled urethane chip.

[0029] In one experimental example, the comparative example using silica, an inorganic porous material, showed that the captured oil was easily leached out due to the low interfacial affinity with asphalt, an organic material, whereas the example using recycled urethane chips, an organic polymer material, stably retained oil inside the pores, resulting in a mass loss rate that was more than 2.5 times lower than that of the inorganic material and significantly superior low-temperature flexural stiffness.

[0030] In step (c) above, this is a process of preparing a third mixture by pre-mixing a tackifying resin with process oil to enhance the tack performance of the additive, thereby lowering the melting temperature of the tackifying resin and inducing the final additive to dissolve rapidly within the asphalt binder so that it can immediately exert bonding strength with the aggregate.

[0031] In this specification, "tack-improving resin" is a general term for a viscous material added to improve the initial tackiness and physical bonding strength of an asphalt binder. In this invention, it has significance in reinforcing the bonding strength between the aggregate and the binder and preventing material detachment in the early stages of pavement service and under heavy load conditions.

[0032] Specifically, the adhesive-improving resin may be a petroleum resin, rosin, terpene resin, or coumarone-indene resin, and in the present invention, it may include one or more selected from petroleum resin and rosin, but is not particularly limited thereto.

[0033] In steps (d) and (e) above, this is a process of integrating the individual mixtures obtained in the preceding steps at a specific ratio to obtain an additive base mixture. Subsequently, in order to secure an optimal balance of flexibility, sustained release, and initial tackiness within the asphalt mixture, 80 to 150 parts by weight of the second mixture and 40 to 80 parts by weight of the third mixture may be added to the entire amount of the first mixture prepared, based on 100 parts by weight of the elastic modifier that serves as the standard for the first mixture, and stirred.

[0034] Specifically, the first to third mixtures are introduced into a large fusion mixer and stirred homogeneously, and then, a silica sand mixture in which 100 parts by weight of ethylene vinyl acetate (EVA), 80 to 120 parts by weight of silica sand, and 0.1 to 0.5 parts by weight of process oil are mixed and aged with respect to 100 parts by weight of the elastic modifier can be added sequentially. This corresponds to a structural design intended to ensure ease of storage and uniformity of mixing by optimizing the volume and specific gravity of the additives while assisting in compatibility with asphalt.

[0035] In the above step (f), this is a chemical crosslinking and stabilization step that goes beyond simple physical mixing to induce a chemical reaction under high-temperature fusion stirring conditions to form a robust three-dimensional network structure and block thermal oxidation. Specifically, 0.5 to 4.0 parts by weight of a polyfunctional aziridine-based crosslinking agent and 0.1 to 1.5 parts by weight of a benzofuranone-based lactone derivative are mixed with 100 parts by weight of an elastic modifier in the additive base mixture and fused and stirred at 90 to 130°C.

[0036] In one experimental example, when the crosslinking agent was below the lower limit (0.5 parts by weight), the formation of the network structure was insufficient, resulting in a significant decrease in dynamic stability; when it exceeded the upper limit (4.0 parts by weight), the hardening phenomenon of the asphalt increased brittleness, causing a side effect of a rapid increase in the rate of change in viscosity after aging by more than 45%. In addition, it was confirmed that if the lactone derivative was below the lower limit (0.1 parts by weight), the oxidation prevention efficiency decreased sharply, and if it exceeded the upper limit (1.5 parts by weight), the excess derivative softened the bonding strength, significantly impairing the resistance to plastic deformation. This was determined to be due to the manifestation of a dual synergistic mechanism in which the polyfunctional aziridine-based crosslinking agent forms a network structure to maximize shear resistance, while the benzofuranone-based lactone derivative immediately captures initial carbon radicals to block thermal oxidation at the source.

[0037] In this specification, "polyfunctional aziridine-based crosslinking agent" refers to a crosslinking agent component that induces strong chemical bonding between polymer chains within an asphalt binder. In the present invention, it has significance as a core functional material that maximizes the physical shear resistance and dynamic stability of a pavement by forming a fine and dense three-dimensional network structure within the binder. Specifically, the polyfunctional aziridine-based crosslinking agent may be a compound containing two or more aziridine functional groups within its molecule that can react with carboxyl groups or hydroxyl groups, etc., within the asphalt or modifier, but is not particularly limited thereto.

[0038] In addition, in this specification, "benzofuranon-based lactone derivative" refers to a high-performance carbon-centered radical scavenger component that suppresses thermal oxidation reactions occurring during high-temperature processing and co-working processes. In the present invention, this has technical significance in that it immediately captures initial carbon radicals generated during fusion stirring for the manufacture of additives, thereby fundamentally blocking the thermal oxidation of the binder. Specifically, the benzofuranon-based lactone derivative may include 5,7-di-tert-butyl-3-(3,4-dimethylphenyl)benzofuranon-2-one or derivatives having a similar benzofuranon skeleton, but is not particularly limited thereto.

[0040] Another aspect is to provide an asphalt additive characterized by being manufactured by the above-described manufacturing method. The same details as described above apply equally to the asphalt additive.

[0041] Specifically, the asphalt additive according to the present invention is characterized in that it is in the form of a composite composition in which process oil is microencapsulated inside a porous medium, such as recycled urethane chips, to have a sustained-release function, and a three-dimensional network structure formed by chemical bonding between an elastic modifier and a crosslinking agent is integrated. The present invention has technical significance in that it continuously maintains the low-temperature flexibility of the asphalt mixture and permanently suppresses cracking caused by long-term aging by capturing process oil inside micropores through a porous medium and inducing sustained-release over a long period when exposed to an external environment.

[0042] In addition, the asphalt additive according to the present invention maintains a state in which a benzofuranone-based lactone derivative is homogeneously dispersed within a physical and chemical network structure formed by the reaction of a polymeric elastic modifier and a polyfunctional aziridine-based crosslinking agent through the fusion stirring process of the above manufacturing method.

[0043] In one experimental example, it was confirmed that through this chemical stabilization structure, the rate of change in asphalt viscosity was maintained at an extremely low level of about 10% or less even after long-term aging, while the dynamic stability was significantly improved compared to the case containing only general antioxidants. This was determined to be because a dual synergistic mechanism was inherently present in the additive itself, in which a polyfunctional aziridine-based crosslinking agent forms a network structure to maximize physical shear resistance to heavy loads, and a benzofuranone-based lactone derivative immediately captures initial carbon radicals generated during fusion stirring to block thermal oxidation at the source.

[0044] In addition, the asphalt additive of the present invention preferably has a formulation in the form of pellets or chips to ensure ease of input at the site and storage stability during the production of asphalt mixtures. In one manufacturing example, the fused product is molded into a chip shape with a diameter of 5 mm and a length of 15 mm using a room-temperature extruder, thereby enabling quantitative supply through an automatic feeding device and maximizing rapid dissolution and dispersion efficiency during the asphalt mixing process.

[0046] Another aspect is to provide a method for manufacturing an asphalt mixture having enhanced interfacial bonding strength, comprising the above-mentioned asphalt additive.

[0047] Specifically, the present invention provides a method for manufacturing an asphalt mixture with enhanced interfacial bonding strength, comprising: (a) a step of heating aggregate; (b) a step of heating asphalt; (c) a step of mixing the heated aggregate, asphalt, and an asphalt additive manufactured by the above manufacturing method together with a filler; and (d) an interfacial bonding step of mixing a composite surface modifier comprising an organic titanate and a phosphate ester into the asphalt mixture obtained in step (c).

[0048] In steps (a) and (b) above, this is a basic preparation process in which the aggregate forming the framework of the mixture and the asphalt binder binding it are each preheated to completely remove internal moisture and ensure optimal fluidity for mixing.

[0049] In one manufacturing example, aggregate and asphalt were prepared by heating them to a temperature of 100 to 180°C, specifically 100 to 140°C. When the additive according to the present invention is applied, the fluidity and coating properties of the binder can be sufficiently secured even in a medium-low temperature environment of 100 to 140°C, where compaction defects previously occurred, thereby enabling uniform mixing between different types of aggregates. Furthermore, even under high-temperature heating conditions of 150 to 180°C, the premature thermal oxidation aging of the asphalt binder can be completely prevented by the crosslinking and anti-oxidation components within the additive, thus providing excellent workability that can be universally applied to both medium-low and high-temperature production conditions.

[0050] In this specification, "aggregate" refers collectively to particulate materials constituting the volume of an asphalt mixture, and in this invention, it can be defined as a technical object for inducing stable bonding even in an environment where artificial aggregates and natural aggregates having different chemical activities are mixed.

[0051] Specifically, the aggregate may include one or more selected from the group consisting of artificial aggregates including ferronickel slag aggregate, blast furnace slag aggregate, steelmaking slag aggregate and fly ash aggregate; natural aggregates including sand, gravel, basalt and black stone; and recycled aggregate, but is not particularly limited thereto.

[0052] In one example of manufacturing, the heated aggregate was applied by mixing ferronickel slag, an artificial aggregate, and basalt, a natural aggregate, in a 1:1 weight ratio. This corresponds to a structural design intended to simultaneously maximize the flow resistance and surface friction resistance of the pavement layer by balancing the two heterogeneous aggregates, which have different surface roughness and physical strength. Furthermore, the heating process has significant technical importance in that it completely evaporates residual moisture present on the surface and in the micropores of these heterogeneous aggregates, thereby activating the surface so that the composite surface modifier can form direct and strong chemical coordination bonds with metal and silicate ions on the aggregate surface without interference from moisture during the subsequent interfacial bonding step.

[0053] In step (c) above, this is a primary stirring process to form a homogeneous asphalt mixture by integrating the heated aggregate, the asphalt binder, and the previously manufactured asphalt additive and filler, and may involve adding and mixing 4 to 7 parts by weight of the heated asphalt, 0.2 to 1.5 parts by weight of the asphalt additive, and 1 to 5 parts by weight of the filler to 100 parts by weight of the heated aggregate.

[0054] In this specification, "filler" refers to a material in the form of fine powder that fills the fine pores of an asphalt mixture and is mixed with a binder to form a mastic state. In the present invention, it has technical significance in that it reinforces the adhesion between aggregate and asphalt and controls the viscosity of the mixture to suppress flow deformation at high temperatures. Specifically, the filler may be stone dust, cement, hydrated lime, or recycled filler, but is not particularly limited thereto.

[0055] In one example of manufacturing, the prepared asphalt additive was introduced into the heated aggregate and asphalt, and a filler was added and homogeneously mixed in a large mixer. This mixing process is intended to create a condition in which the process oil microencapsulated inside the porous medium is not lost and remains stable despite the mechanical shear force and heat of the large mixer by introducing the asphalt additive into the environment of aggregate and asphalt heated to a high temperature, and can be gradually released by vehicle load during future pavement service. In particular, the addition of a filler during mixing corresponds to a structural design intended to create an environment in which fine powder particles fill the rough surface pores of the aggregate while simultaneously increasing the viscosity of the asphalt binder to an appropriate level, thereby ensuring that the modifying components derived from the additive are not lost to the outside of the mixture but are stably fixed and dispersed at the interface between the aggregate and the binder within the large mixer.

[0056] In step (d) above, this is an interfacial bonding step to maximize the chemical interfacial bonding strength between the aggregate and the binder in an asphalt mixture mixed with heterogeneous aggregates. Specifically, this involves mixing 0.5 to 2.5 parts by weight of a composite surface modifier in which organic titanate and phosphate ester are mixed in a weight ratio of 1:1 to 1:3 with respect to 100 parts by weight of the asphalt.

[0057] The organic titanate component in this composite surface modifier forms coordination bonds with transition metals on the surface of artificial aggregates, and the phosphate ester component exhibits strong chemical affinity with the silicate component of natural aggregates. By forming a strong and stable adhesive interface for both types of aggregates with completely different surface roughness and chemical properties, it has technical significance in fundamentally preventing the loss of bonding strength and delamination between aggregates and binders that occurs upon moisture penetration.

[0058] In one experimental example, it was confirmed that the examples applied by adjusting the component weight ratio of the composite surface modifier to 1:1 to 1:3 and the input content to within a critical range of 0.5 to 2.5 parts by weight demonstrated excellent interfacial bonding performance, with the tensile strength ratio (TSR) before and after immersion in a water tank exceeding 0.90 and the cantabro loss rate, which indicates detachment of surface aggregate, being significantly low in the 3-6% range.

[0060] Another aspect provides an asphalt mixture manufactured by the above-described manufacturing method, characterized by being selectively applicable to modified, low-noise drainage and low-noise non-drainage, SMA, PSMA, hybrid, waterproofing, and regenerative applications. The same details described above apply equally to the above-described asphalt mixture.

[0061] Specifically, the asphalt mixture according to the present invention provides excellent scalability by adjusting the particle size distribution of aggregates and the mixing ratio of additives to suit site purposes, thereby enabling universal application to a diverse range of special functional paving product families (modification, low-noise drainage and low-noise non-drainage, SMA, PSMA, hybrid, waterproofing, recycling, etc.) using only a single additive.

[0062] In this specification, “Modified” refers to a form in which a polymeric elastic modifier is added to an asphalt binder to improve performance. In this invention, the three-dimensional network structure formed through a polyfunctional aziridine-based crosslinking agent in the additive has significance in maximizing resistance to plastic deformation and flow resistance in heavy-load roads.

[0063] In this specification, “low-noise drainage and low-noise non-drainage” may refer, depending on the type, to pavement that absorbs friction noise by securing a void ratio of 12% or more for low-noise non-drainage, and pavement that rapidly drains rainwater and reduces tire friction noise by securing a void ratio of 16% or more for low-noise drainage. The present invention has technical significance in that a composite surface modifier forms a strong chemical interfacial bond with the aggregate surface to fundamentally prevent aggregate detachment, which commonly occurs in permeable pavements with large voids, while a benzofuranone-based lactone derivative blocks the thermal oxidation hardening of the binder, thereby maintaining the flexibility and adhesion of the asphalt binder for a long period even in permeable structures with developed voids.

[0064] In this specification, “Mastic Asphalt” and “PSMA (Polymer-modified SMA)” may refer to a pavement type (void ratio of about 1 to 4%) that maximizes crack resistance through the interlocking effect of coarse aggregates and a large amount of asphalt mastic. In the present invention, the process oil and high-performance tackifying resin included in the additives dramatically strengthen the bonding force between a large amount of aggregates and mastic, thereby performing a key function of stably maintaining the interlocking framework between aggregates even in high temperature and heavy load environments.

[0065] In this specification, “waterproof” may refer to a dense paving form with a porosity of 2% or less, applied to structures such as bridge decks or underpasses where moisture penetration must be completely blocked. In this invention, process oil trapped in a porous medium is released in a sustained-release manner to maintain the flexibility of the binder for a long period, thereby preemptively blocking moisture penetration through microcracks, and provides an auxiliary synergistic effect that completely overcomes moisture vulnerability through a composite surface modifier based on organic titanate and phosphate ester.

[0066] In this specification, “Hybrid” refers to a high-performance fused packaging form that combines two or more characteristics, such as the modification, drainage, SMA, and waterproofing, to meet the requirements of a public environment, but is not specifically limited thereto.

[0067] In this specification, “Recycling” may refer to an eco-friendly paving form in which waste asphalt concrete (recycled aggregate) is mixed with new aggregate and binder for recycling. The present invention has technical significance in that plastic components, such as process oil, which were encapsulated in a porous medium within the additive, effectively soften and regenerate the oxidized and hardened waste asphalt binder, thereby restoring physical properties and fatigue crack resistance equivalent to those of new asphalt.

[0068] The asphalt mixture according to the present invention comprises a state in which active ingredients, such as process oil, which were microencapsulated within the additive, are stably preserved within a porous medium despite the mechanical shear force and heat of a large mixer. Furthermore, it is characterized in that fine powder particles of the introduced filler fill the rough surface pores of the aggregate and, at the same time, are mixed with the asphalt binder to form a mastic state in which viscosity is maintained at an appropriate level.

[0069] In particular, the above asphalt mixture is characterized by the application of a composite surface modifier mixed with organic titanate and phosphate ester, thereby ensuring perfect chemical interfacial bonding strength even in environments where heterogeneous aggregates, such as artificial aggregates and natural aggregates, are mixed. Specifically, the organic titanate component in the composite surface modifier forms a coordination bond with the transition metal on the surface of artificial aggregates such as ferronickel slag, and the phosphate ester component can exhibit strong chemical affinity with the silicate component of natural aggregates such as basalt, thereby enabling the formation of a strong and stable adhesive interface for all heterogeneous aggregates with completely different surface roughness and chemical properties.

[0071] Another aspect is to provide an asphalt construction method using the above-described asphalt mixture. The same details as described above apply equally to the above-described asphalt construction method.

[0072] Specifically, the present invention provides an asphalt construction method comprising: (a) a step of leveling the construction surface and removing impurities to form a construction section; (b) a step of laying the asphalt mixture on top of the construction section; (c) a step of compacting the asphalt mixture after laying; and (d) a step of curing.

[0073] In the above steps (a) and (b), this is a process that forms the basis for paving construction, and involves laying a previously manufactured asphalt mixture with enhanced interfacial bonding strength to a uniform thickness on a construction surface from which impurities have been removed and which has been leveled, thereby preparing an optimal condition for a subsequent compaction step.

[0074] In step (c) above, this corresponds to a step of applying physical pressure before the temperature of the laid asphalt mixture cools to densely fill the internal micro-pores and stably secure the density and surface flatness of the pavement layer. Specifically, this can be subdivided into primary compaction to form the initial framework of the mixture, secondary intermediate compaction to maximize interlocking between aggregates through vibration frequency, etc., and tertiary flatness compaction to remove roller marks and irregularities to finish the surface smoothly, but is not particularly limited thereto.

[0075] In addition, depending on the functionality of the mixture to be laid (SMA, drainage, waterproofing, etc.) or the topographical conditions of the site, a skilled technician in the industry may apply equipment and methods widely known in the industry, such as combination rollers and small vibratory rollers, to suit the purpose.

[0076] In the above step (d), this refers to the process of finally completing the construction of the asphalt pavement, and involves cooling and hardening the asphalt pavement layer, after the compaction step is completed, so that it can exhibit sufficient load-bearing capacity and structural stability against heavy loads before actual traffic opening.

[0077] Specifically, this may be a stage of temperature reduction and curing until the surface temperature of the pavement layer drops sufficiently to a stable level (about 40°C or lower) under ambient temperature conditions, which does not cause deformation, but is not specifically limited thereto. However, depending on site conditions such as night construction in urban areas where rapid traffic opening is required, various accelerated curing methods generally used in the industry, such as surface water cooling using a water truck or forced air cooling using a large blower, may be applied at the discretion of a skilled technician in the industry. Effects of the invention

[0079] The asphalt additive according to the present invention induces the sustained release of oil through a porous medium, thereby maintaining the low-temperature flexibility of the asphalt even after long-term use and significantly extending its lifespan.

[0080] In addition, through the dual synergy of the crosslinking agent and the antioxidant in the additive, a three-dimensional network structure is densely formed inside the binder and thermal oxidation is blocked at the source, thereby improving dynamic stability under heavy loads and fundamentally suppressing plastic deformation and the occurrence of potholes.

[0081] Furthermore, the asphalt mixture of the present invention provides excellent structural stability that completely prevents the detachment and spalling of aggregates even in moisture-vulnerable environments by applying a composite surface modifier to maximize the chemical interfacial bonding strength between heterogeneous aggregates, such as artificial aggregates and natural aggregates. Specific details for implementing the invention

[0083] The following examples will be explained in more detail. However, these examples are for illustrative purposes only and the scope of the present invention is not limited to these examples.

[0085] Preparation Example 1. Preparation of the high-durability asphalt additive for medium-low and high temperatures according to the present invention

[0086] First, 100 kg of styrene-butadiene-styrene (SBS), an elastic modifier, was mixed with 20 kg of naphthenic process oil and 5 kg of plasticizer (DOA) and aged for 24 hours to prepare a first mixture of 125 kg in total. Separately, 15 kg of process oil was mixed with 100 kg of recycled urethane chips, a porous medium, and aged to prepare a second mixture of 115 kg in total, and 50 kg of petroleum resin and 10 kg of process oil were mixed to prepare a third mixture of 60 kg in total.

[0087] In the subsequent mixing process, based on 100 kg of the elastic modifier (SBS) that serves as the standard for the first mixture, 115 kg of the second mixture and 60 kg of the third mixture were fed into a large fusion mixer to homogeneously mix the entire amount (125 kg) of the prepared first mixture.

[0088] 100 kg of ethylene vinyl acetate (EVA), which melts at 100°C or lower, was mixed into the above-mentioned stirred product, and a silica sand mixture coated and absorbed with 0.3 kg of process oil was added to 100 kg of silica sand as an extender to obtain an additive base mixture. Subsequently, to provide structural stability through chemical crosslinking, 1.5 kg of a polyfunctional aziridine-based crosslinking agent and 0.5 kg of a benzofuranone-based lactone derivative were added to the additive base mixture based on 100 kg of the above-mentioned elastic modifier (SBS).

[0089] The above mixture was heated and fused at a temperature of 110°C for 2 hours to form a three-dimensional network structure inside the asphalt. Finally, the fused product was molded and cut into chip shapes with a diameter of 5 mm and a length of 15 mm using a cold extruder to complete the final granular asphalt additive.

[0091] Preparation Example 2. Preparation of the asphalt mixture with enhanced interfacial bonding strength according to the present invention

[0092] First, asphalt heated to a temperature of 100 to 140°C and heated aggregate were prepared. At this time, the aggregate was prepared by mixing ferronickel slag, an artificial aggregate, and basalt, a natural aggregate, in a 1:1 weight ratio. In the subsequent first mixing process, 5 kg of the heated asphalt and 0.5 kg of the asphalt additive prepared in Preparation Example 1 were added to 100 kg of the heated aggregate (specifically 50 kg of ferronickel slag and 50 kg of basalt), and 3 kg of filler for filling fine pores in the mixture was added and homogeneously mixed in a large mixer.

[0093] Subsequently, in the second mixing process, an interfacial bonding step was performed in which 0.5 to 2.5 parts by weight of a composite surface modifier, in which organic titanate and phosphate ester are mixed in a weight ratio of 1:1 to 1:3 with respect to 100 parts by weight of the asphalt, was uniformly sprayed and mixed using a liquid spraying device to ensure perfect interfacial bonding strength even in an environment where artificial aggregate and natural aggregate are mixed. Through this process, the organic titanate component in the composite surface modifier forms a coordination bond with the transition metal on the surface of the artificial aggregate, and the phosphate ester component exhibits a strong chemical affinity with the silicate component of the natural aggregate, thereby finally obtaining an asphalt mixture that forms a strong adhesive interface for both types of aggregates with different properties.

[0095] Preparation Example 3. Construction using the asphalt mixture of the present invention

[0096] The existing pavement surface was cut to level the construction surface, and dust and impurities on the surface were completely removed using a road cleaning vehicle to prepare the construction section. Subsequently, the asphalt mixture heated and mixed at a temperature of 100 to 140°C according to Manufacturing Example 2 was uniformly laid on the prepared construction section to a constant thickness of about 5 cm using an asphalt finisher. After the laying was completed, a compaction step was performed before the temperature of the mixture cooled. Specifically, for the first compaction, a Macadam roller was used to perform initial compaction of the mixture and form a framework. Subsequently, for the second compaction, a tire roller was used to apply vibration at 20 to 30 Hertz (Hz) to densely fill the fine voids between the aggregates, and finally, a tandem roller was used to perform flatness compaction to eliminate irregularities and finish the surface smoothly. Afterwards, the pavement layer underwent a natural curing process for 24 hours at room temperature until the surface temperature dropped sufficiently to the ambient temperature level (about 40℃ or lower), thereby finally completing the construction of the asphalt pavement with load-bearing capacity and structural stability.

[0098] Experimental Example 1-1. Evaluation of Sustained-Release Encapsulation of Process Oil and Low-Temperature Cracking Resistance Using a Porous Medium

[0099] To verify the mechanism by which the asphalt additive according to the present invention prevents thermal oxidation hardening of asphalt occurring during service and permanently suppresses low-temperature cracking, a performance evaluation was performed by controlling the type of medium and the oil injection method as single variables.

[0100] Specifically, the processes of Preparation Example 1 and Preparation Example 2 were performed identically, but asphalt mixtures were prepared as samples by varying the porosity of the medium containing the process oil and whether the oil was pre-aged. For each sample, to simulate long-term service conditions, accelerated aging was performed for 20 hours at 100°C and 2.1 MPa using a Pressure Aging Vessel (PAV), and the mass loss rate (%) due to oil volatilization was measured. The aged asphalt binder was extracted, and the flexural stiffness (standard value 300 MPa or less) was measured in a cryogenic environment of -20°C using a BBR (Bending Beam Rheometer, KS F 2392) to evaluate low-temperature crack resistance.

[0101] [Table 1-1]

[0102]

[0104] As a result, it was confirmed that Examples 1-1 to 1-3, in which process oil was impregnated onto porous recycled urethane chips according to the present invention and aged for 20 to 30 hours, simultaneously achieved overwhelmingly superior low-temperature flexibility and long-term aging resistance compared to the control group and comparative examples. In particular, even among porous media that underwent the same 24-hour aging process, a clear difference in performance was observed depending on the characteristics of the material. In the case of Comparative Example 1-3, which used silica, an inorganic porous material, the oil capture ability was partially improved compared to non-porous silica sand, but compared to Example 1-2, which used recycled urethane chips made of an organic polymer material, the mass loss rate was more than 2.5 times higher and the flexural stiffness was also significantly inferior. This was determined to be because, while the captured oil showed a limitation of easily leaching out when exposed to the external environment due to the low interfacial affinity between inorganic silica and organic asphalt, organic recycled urethane chips, which exhibit chemically similar behavior to asphalt, more stably retained oil within the pores and flexibly distributed the bending stress of the entire pavement when a load was applied through their own elasticity.

[0105] In addition, when examining the criticality according to changes in aging time, the comparative example aged for 10 hours or less showed minimal improvement in sustained-release performance due to insufficient physical residence time for oil to penetrate into the micropores of the urethane chip; however, in the examples aged for 20 hours or more, the mass loss rate decreased sharply to less than 0.15%, exhibiting a perfect microencapsulation effect. However, in the comparative example aged for more than 30 hours, it was confirmed that the additional performance improvement reached a saturation state. From this, it was proven that an aging process of 20 to 30 hours for oil absorption within the medium is an essential critical configuration to maximize the synergy of sustained-release oil using a porous medium and simultaneously satisfy process efficiency and low-temperature crack prevention performance.

[0107] Experimental Example 1-2. Confirmation of dynamic stability and viscosity change rate after long-term aging according to the blending content of polyfunctional aziridine-based crosslinking agent and benzofuranone-based lactone derivative

[0108] In order to derive the optimal chemical mixing ratio to maximize the pothole prevention and aging resistance performance of the asphalt additive according to the present invention, the process of Manufacturing Example 1 and Manufacturing Example 2 was performed identically, but the input content of the polyfunctional aziridine-based crosslinking agent and benzofuranone-based lactone derivative introduced during the additive manufacturing process was varied, and asphalt mixtures of each treatment group (Examples 1-4 to 1-6 and Comparative Examples 1-7 to 1-13) were prepared and performance evaluated.

[0109] Specifically, to evaluate resistance to plastic deformation (pothole prevention performance), a wheel tracking test was performed according to KS F 2374 at 60°C to calculate dynamic stability (cycles / mm). Separately, to evaluate the hardening phenomenon of the asphalt due to long-term serviceability, long-term aging was induced for 20 hours at 100°C and 2.1 MPa using a pressure aging tester (PAV), and the absolute viscosity at 60°C before and after aging was measured to calculate the percentage change in viscosity. The content conditions and test results for each example and comparative example are shown in Table 1-2 below (however, the content of the polyfunctional aziridine-based crosslinking agent and benzofuranon-based lactone derivative is based on 100 parts by weight of the elastic modifier (SBS) of Preparation Example 1 above).

[0110] [Table 1-2]

[0111]

[0113] As a result, Examples 1-4 to 1-6 of the present invention showed a significant effect in that the dynamic stability was improved by up to 2.6 times or more compared to Comparative Example 1-7, to which only a conventional general antioxidant was applied, and the rate of change in viscosity after aging was suppressed to a level of about 10% or less. This is believed to be because a dual synergistic mechanism was exhibited in which a polyfunctional aziridine-based crosslinking agent densely forms a three-dimensional network structure inside the asphalt to maximize physical shear resistance, while a benzofuranone-based lactone derivative immediately captures initial carbon radicals generated during fusion stirring to block thermal oxidation at the source.

[0114] On the other hand, comparative examples in which the content of each additive fell outside the scope of the present invention showed distinct limitations in specific indicators. Specifically, Comparative Example 1-10, in which the crosslinking agent was added at a level below the lower limit, showed insufficient heavy load bearing capacity as a sufficient network structure was not formed, resulting in a dynamic stability of only 2,105 revolutions / mm. Conversely, Comparative Example 1-11, in which the crosslinking agent exceeded the upper limit, showed increased brittleness due to excessive hardening of the asphalt, causing the viscosity change rate after aging to surge to 45.12% and resulting in the side effect of easily breaking.

[0115] In addition, Comparative Example 1-12, in which the lactone derivative was added at a lower limit, showed a sharp decrease in anti-aging efficiency (19.55%) as the network structure formed by the crosslinking agent was partially oxidized in the early stages, and in Comparative Example 1-13, in which the upper limit was exceeded, the excess derivative material acted like a plasticizer within the asphalt, softening the bonding strength and resulting in a significant decrease in dynamic stability to 2,352 cycles / mm.

[0116] From this, it was confirmed that in order to maximize the chemical bonding strength within the asphalt additive to prevent potholes and simultaneously satisfy long-term aging resistance, the combination of 0.5 to 4.0 parts by weight of a polyfunctional aziridine-based crosslinking agent and 0.1 to 1.5 parts by weight of a benzofuranone-based lactone derivative per 100 parts by weight of an elastic modifier is an essential critical range.

[0118] Experimental Example 2. Verification of tensile strength ratio and stripping resistance of asphalt mixtures according to the mixing ratio and input content of composite surface modifiers

[0119] Performance evaluations were performed to demonstrate that the asphalt mixture according to the present invention exhibits perfect interfacial bonding strength even in an environment where artificial aggregates and natural aggregates are mixed, and to determine the optimal mixing ratio and critical content of the composite surface modifier for this purpose.

[0120] Specifically, the asphalt mixture manufacturing process of Manufacturing Example 2 was performed in the same manner, but the component weight ratio (organic titanate: phosphate ester) of the composite surface modifier added during the second stirring was divided into five groups, and within each group, the total input content of the surface modifier was cross-designed under three conditions to produce a total of 15 asphalt mixture specimens. For all specimens, the aggregate was prepared by mixing ferronickel slag and basalt in a 1:1 weight ratio.

[0121] To evaluate the resistance of the manufactured mixture specimens to the loss of bonding strength (striping) between the aggregate and asphalt due to moisture penetration, the indirect tensile strength was measured before and after immersion in a water tank according to KS F 2398, and the Tensile Strength Ratio (TSR) was calculated. Separately, to evaluate the resistance of the surface aggregate to physical stripping, a Cantabro test was performed at 20°C according to KS F 2382, and the loss rate (%) was calculated. The content conditions and test results for each example and comparative example are shown in Table 2 below (provided that the content is in parts by weight relative to 100 parts by weight of asphalt).

[0122] [Table 2]

[0123]

[0125] As a result, Examples 2-1 to 2-3, which satisfy the component mixing ratio and total input content of the present invention, demonstrated excellent interfacial bonding performance by having a tensile strength ratio exceeding 0.90 and a significantly low cantabro loss rate of 3 to 6%. This was determined to be because the organic titanate formed a coordination bond with the transition metal on the surface of the artificial aggregate (slag), and the phosphate ester exhibited a strong chemical affinity with the silicate component of the natural aggregate, thereby forming a strong adhesive interface between two types of aggregates with different properties.

[0126] On the other hand, Comparative Examples 2-2 and 2-11, in which the ratio conditions were inappropriate, failed to reach the quality standard value (0.85) for the tensile strength ratio because delamination occurred intensively at either the interface between the artificial aggregate or the natural aggregate due to a lack of specific components. In addition, Comparative Examples 2-4, 2-6, and 2-8, in which the input amount was below the lower limit even with appropriate ratios, failed to induce sufficient interfacial bonding due to an absolute lack of reactive elements, while Comparative Examples 2-5, 2-7, and 2-9, in which the input amount exceeded the upper limit, showed a phenomenon in which unreacted modifier components hindered the aggregation of asphalt, resulting in a slight decrease in physical properties.

[0127] From this, it was confirmed that in order to secure perfect interfacial bonding strength in a general aggregate environment, it is essential to limit the component weight ratio of the composite surface modifier to 1:1 to 1:3 under the process conditions of Preparation Example 2 above, and to control the input content within a critical range of 0.5 to 2.5 parts by weight.

[0129] Experimental Example 3. Comparison of Compaction Quality and Thermal Oxidation Aging Resistance of Asphalt Mixtures under Medium-Low and High Temperature Production Conditions

[0130] In order to demonstrate that the asphalt additive according to the present invention can exhibit mixture quality and long-term durability equivalent to or better than high-temperature production conditions of 150 to 180°C even under medium-low temperature production conditions of 100 to 140°C, a performance evaluation was performed using a cross-design method in which the type of additive and the mixture production temperature were controlled as single variables.

[0131] Specifically, based on the formulation design of Manufacturing Example 2 above (aggregate mixed in a 1:1 weight ratio of ferronickel slag and basalt, asphalt content 5 wt%), the same method was applied, but the type of additive (asphalt additive of Manufacturing Example 1 according to the present invention, conventional wax-based additive for medium-low temperature, no additive) and the asphalt mixture production temperature (medium-low temperature condition of 120°C and high temperature condition of 160°C) were cross-designed to produce a total of 5 asphalt mixture specimens as samples. For the conventional wax-based additive for medium-low temperature, a commercially available additive was used that enables medium-low temperature mixing production by melting at high temperatures and temporarily reducing the viscosity of the asphalt binder.

[0132] To evaluate the compaction quality of the prepared mixture specimens, a Marshall test was performed according to KS F 2337 to calculate the porosity (%) and Marshall stability (kN). In addition, to evaluate resistance to plastic deformation, a Wheel Tracking test according to KS F 2374 was performed at 60°C to calculate the dynamic stability (cycles / mm). Furthermore, to evaluate the vulnerability of the binder to thermal oxidation aging due to long-term use, accelerated aging was performed for 20 hours at 100°C and 2.1 MPa using a pressure aging tester (PAV). The absolute viscosity at 60°C before and after aging was measured to calculate the percentage change in viscosity (%). The conditions and test results for each treatment group are shown in Table 3 below.

[0133] [Table 3]

[0134]

[0136] As a result, Example 3-1, produced under medium-low temperature conditions of 120°C using the asphalt additive of the present invention, achieved a void ratio of 4.0%, Marshall stability of 12.5 kN, dynamic stability of 4,486 revolutions / mm, and a viscosity change rate of 4.3% after aging, and it was confirmed that it was substantially equivalent in all performance indicators to Example 3-2 (void ratio 3.9%, Marshall stability 12.8 kN, dynamic stability 4,605 ​​revolutions / mm, viscosity change rate 4.7%) produced using the same additive under high temperature conditions of 160°C.

[0137] On the other hand, Comparative Example 3-1, produced at high temperature without additives, showed good compaction quality, but the viscosity change rate after aging reached 31.4%, resulting in significantly inferior long-term durability. This is consistent with the results of the preceding Experimental Example 1-2 and reaffirms the structural limitations of the conventional high-temperature production method that lacks an anti-oxidation function. Comparative Example 3-2, produced at medium-low temperature without additives, saw its porosity skyrocket to 7.4% due to increased binder viscosity and its dynamic stability remained at 1,045 cycles / mm, falling far short of the paving quality standards. Comparative Example 3-3, which applied a conventional wax-based additive, showed some improvement in processability, but its dynamic stability (1,842 cycles / mm) and viscosity change rate (21.2%) were still significantly inferior to those of the embodiments of the present invention.

[0138] From this, it was confirmed that the asphalt additive according to the present invention can exhibit equally excellent mixture quality across a wide range of production temperature conditions, ranging from low to medium temperatures of 100 to 140°C to high temperatures of 150 to 180°C, by ensuring sufficient coating properties and fluidity of the binder under medium-low temperature conditions through the process oil supported on a porous medium, while completely suppressing early thermal oxidation occurring during high-temperature production through the dual synergy of a crosslinking agent and a lactone derivative.

[0140] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.

Claims

Claim 1 A method for manufacturing a high-durability asphalt additive for both medium-low and high temperatures, comprising: (a) a step of preparing a first mixture by mixing 10 to 30 parts by weight of process oil and 3 to 7 parts by weight of a plasticizer with 100 parts by weight of an elastic modifier and aging the mixture; (b) a step of preparing a second mixture by mixing 5 to 30 parts by weight of process oil with 100 parts by weight of a porous medium containing recycled urethane chips and aging the mixture for 20 to 30 hours; (c) a step of preparing a third mixture by mixing 10 to 30 parts by weight of process oil with 100 parts by weight of a tackifying resin; (d) a step of mixing 80 to 150 parts by weight of the second mixture and 40 to 80 parts by weight of the third mixture into the first mixture and stirring the mixture based on 100 parts by weight of the elastic modifier; (e) adding 50 to 150 parts by weight of ethylene vinyl acetate (EVA) to the stirred product with respect to 100 parts by weight of the elastic modifier A method for manufacturing an asphalt additive, comprising: (f) a step of mixing by weight and adding an aged silica sand mixture in which 0.1 to 0.5 parts by weight of process oil are mixed with 100 parts by weight of silica sand to obtain an additive base mixture; and (f) a chemical crosslinking and stabilization step comprising adding 0.5 to 4.0 parts by weight of a polyfunctional aziridine-based crosslinking agent and 0.1 to 1.5 parts by weight of a benzofuranone-based lactone derivative to the additive base mixture based on 100 parts by weight of the elastic modifier, and fusing and stirring at a temperature of 90 to 130°C. Claim 2 Asphalt additive characterized by being manufactured by the manufacturing method of claim 1. Claim 3 A method for manufacturing an asphalt mixture comprising: (a) a step of heating aggregate; (b) a step of heating asphalt; (c) a step of mixing the heated aggregate, asphalt, and an asphalt additive manufactured by the method of claim 1 together with a filler; and (d) an interfacial bonding step comprising mixing a composite surface modifier, in which organic titanate and phosphate ester are mixed in a weight ratio of 1:1 to 1:3, into the asphalt mixture obtained in step (c) in an amount of 0.5 to 2.5 parts by weight per 100 parts by weight of the asphalt. Claim 4 An asphalt mixture manufactured by the manufacturing method of claim 3, characterized by being selectively applicable among modified, low-noise drainage and low-noise non-drainage, SMA, PSMA, hybrid, waterproofing, and regeneration. Claim 5 A construction method using an asphalt mixture according to paragraph 4, comprising: (a) a step of leveling the construction surface and removing impurities to form a construction section; (b) a step of laying the asphalt mixture on top of the construction section; (c) a step of compacting the asphalt mixture after laying is completed; and (d) a step of curing.

Citation Information

Patent Citations

  • Additive composition for asphalt admixture and its blend

    JP1989284557A

  • Natural polyol-organic / inorganic hybrid composite concrete with excellent elasticity and durability used in joint gap (asphalt, concrete) of civil engineering structure and construction method usin the same

    KR101838528B1

  • Stabilization of thermoplastic nanocomposites

    KR1020050105438A

  • Medium-Low temperature asphalt additive that can be used even at high temperatures and its manufacturing method, and asphalt mixture using the same and its manufacturing method

    KR1020230106769A

  • Permeable high grade asphalt concrete composition having excellennt adhesive property and constructing method using the same

    KR102154567B1